Early Rehabilitation for the Prevention and Management of Pleural Empyema: A Narrative Review - Arnengsih Nazir; Marietta Shanti Prananta; Ami Rachmi; Vecky Ferjuniko (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Parapneumonic effusions (PPE) can progress to pleural empyema (PE), a severe condition associated with increased morbidity and mortality. Pleural empyema impairs lung function due to pleural inflammation, fluid accumulation, and restricted diaphragm movement. Patients with severe PPE and PE often require intensive care, where prolonged immobilization and mechanical ventilation further exacerbate respiratory decline. Early rehabilitation (ER) has shown promise in reducing complications associated with prolonged intensive care unit (ICU) stays, but its role in preventing PE remains unclear. This review aimed to assess the impact of ER on PE prevention and on clinical outcomes. Methods: A literature search was conducted using PubMed and Google Scholar, focusing on original research and case reports related to PE, ICU care, and ER interventions. Only full-text English articles were included. Results: Ten studies met the inclusion criteria, comprising four original research articles and six case reports. Early rehabilitation, including respiratory physiotherapy, early mobilization, and targeted exercises, has been shown to enhance lung expansion, prevent atelectasis, and reduce postoperative pulmonary complications. It also improved oxygenation, secretion clearance, functional capacity, and psychological well-being. Patients receiving structured ER programs had shorter hospitalizations and better overall outcomes. Conclusion: Early rehabilitation plays a crucial role in mitigating respiratory complications in critically ill patients by reducing the incidence of PE, improving pulmonary mechanics, and preventing pleural adhesions. While further large-scale studies are needed, current evidence supports integrating ER into ICU protocols to optimize respiratory function, enhance recovery, and improve quality of life in patients at risk of PE.